PENGARUH STRUKTUR MODAL, STRUKTUR KEPEMILIKAN DAN UMUR PERUSAHAAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL - Heri Budisusetyo; Ika Wahyuni; Ferdinandus Kusuma; Mentari Wahyuningsih (Jurnal Akuntansi Trisakti, 2022)
This study aims to determine the effect of the company's capital structure, company ownership structure and company age on the disclosure of social responsibility. This study uses a sample of manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2019 period. A total of 41 companies were sampled in this study. The sampling technique used in this study was purposive sampling with predetermined criteria. The data used are in the form of financial reports and/or financial reports obtained from the IDX official website or reports from the company's website in the form of annual reports or sustainability reports. The results show that capital structure has no effect on CSR, institutional ownership has a negative effect on CSR. while foreign ownership and company age have a positive effect on CSR. The results of this study support the stakeholder theory and agency theory where a certain group of people has a great influence on the survival of the company.Keywords : capital structure; company ownership; structure company age; CSR